Proposed new design scheme of BMW Motorrad Malaysia for Wunderlich Sales & Service Sdn. Bhd. at Lot 34 Jalan Robson, Robson Height, Kuala Lumpur / Nur Nabilah Ab. Karim - Ab. Karim, Nur Nabilah (Faculty of Architecture, Planning and Surveying, 2010)
Project Report is one of the subject which had to be taken by student part six(06) in Diploma Interior Design in order to graduate and passed. This course as a practice for student to do their research based on their project proposed and fullfill all the requirement needed. This project report is a report on a new proposal which is proposed new design scheme of BMW Motorrad lifestyle boutique for Wunderlich Sale & Service Sdn. Bhd. as a Diploma Interior Design final project. The aim of this lifestyle boutique for the riders and new user of BMW motorrad or for them who just want to chill-out at the boutique as their lifestyle and its open daily to public. The boutique comes with lounge and bar cafe, which they can spend their day there by absorbing the new accesories from BMW Motorrad and new motorcycles. The lifestyle boutique is also a service center for BMW Motorrad that will ease the rider to service after a long journey. Beside that, it also offers a space for group gathering sessions across the country and also an information area to get latest event from BMW Motorrad. The company has therefore established ecological and social sustainability throughout the value chain, comprehensive product responsibility and a clear commitment to conserving resources as an integral part of its strategy. On top of that, the design that is required by the client is a sophisticated design that shows the identity of motorcycles or a new modern design but still keep the BMW concept. Comprising of a boutique, services center and a spot for BWM motorrad around the country, the space is intended to provide a touch point for its viewers.